2018
DOI: 10.1155/2018/4972070
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Co and Pt-Ni Catalysts of Low Metal Content for H2 Production by Reforming of Oxygenated Hydrocarbons and Comparison with Reported Pt-Based Catalysts

Abstract: New catalysts of Pt, PtNi, PtCo, and NiCo supported on Al 2 O 3 were developed for producing hydrogen by aqueous phase reforming (APR) of oxygenated hydrocarbons. e urea matrix combustion technique was used for loading the metal on the support in order to improve several aspects: increase both the metal-support interaction and the metal dispersion and decrease the metal load. e catalysts were characterized by MS/ICP, N 2 adsorption, XRD, TPR, CO chemisorption, and the test of cyclohexane dehydrogenation (CHD).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…The first maximum would correspond to the reduction of platinum complex deposited on the surface of the carbonaceous support and not located near metal particles [39,40] whereas that at high temperature is attributable to the gasification of the carbonaceous support catalyzed by the Pt particles [41][42][43]. This second peak shifts to lower temperatures when platinum is present due to the platinum spillover effect [44]. It can be also observed that as the metal loading increases, and therefore the crystallite size, reduction profiles move to lower temperatures.…”
Section: Physicochemical Characterization Of Pt-m/c-02 Cathodesmentioning
confidence: 98%
“…The first maximum would correspond to the reduction of platinum complex deposited on the surface of the carbonaceous support and not located near metal particles [39,40] whereas that at high temperature is attributable to the gasification of the carbonaceous support catalyzed by the Pt particles [41][42][43]. This second peak shifts to lower temperatures when platinum is present due to the platinum spillover effect [44]. It can be also observed that as the metal loading increases, and therefore the crystallite size, reduction profiles move to lower temperatures.…”
Section: Physicochemical Characterization Of Pt-m/c-02 Cathodesmentioning
confidence: 98%